The influence of HIV and ART exposure on neonate brain volumes - Olagunju, Aishah (Department of Human Biology, 2024)
Introduction: There is growing evidence that maternal health in pregnancy influences the infant neurodevelopment. However, there are limited studies including broad metrics of maternal health when studying typical and atypical infant neurodevelopment. Although the human immunodeficiency virus (HIV) is a global pandemic, South Africa has the biggest and most high-profile HIV epidemic. Over the past decade, South Africa has reduced vertical transmissions of HIV, from improvements in antiretroviral medicines and the widespread accessibility of prevention programs. An outcome of this achievement is an increasing population of HIV-exposed-uninfected (HEU) infants and children. Despite improved outcomes compared to their peers living with HIV, HEU infants and children are at risk of neurodevelopmental delays in relation to HIV–unexposed–uninfected (HUU) children. As a result, there is a need to better understand the outcome of HIV/ART exposure on the fetal/infant/child brain. This study aimed to investigate the effect(s) of HIV and duration of ART exposure and the potential impact of additional maternal health factors during pregnancy on neonate brain volumes. Methods: Using magnetic resonance imaging (MRI), T1-weighted brain images of neonates were acquired. Infants included those whose mothers initiated ART preconception (HEU-pre), those whose mothers initiated ART post-conception (HEU-post) and infants born to mothers living without HIV or HIV unexposed uninfected (HUU). The data were quality checked and volumes were determined using the infant FreeSurfer tool. Statistical analysis was done in R to identify maternal health factors related to neonatal volumes as well as volumetric group differences due to HIV and ART exposure. Results: This analysis included 151 infants (49 HEU-pre; 48 HEU-post; 54 HUU; mean age 1.8 weeks; 50.3% male). Across all newborns, maternal Harvard Trauma Questionnaire (HTQ) score during pregnancy was associated with bilateral amygdala volumes. Within HEU infants, maternal CD4 count was associated with right thalamus and caudate volumes bilaterally. Group analysis showed a significant decrease in mean caudate volume bilaterally in the HEUpost group (left hemisphere p=0.006; right hemisphere p=0.009), as well as reduced right amygdala volume after controlling for maternal HTQ assessed in pregnancy. There was also a significant increase in the left lateral ventricle (p=0.04) and a decrease in the left cerebral white matter of HEU-pre infants (p=0.03). Conclusion: This study observed volumetric differences in HEU infants dependent on timing of maternal ART initiation, maternal immune health and maternal trauma assessed during pregnancy.